Injectable nanofibrous spongy microspheres for NR4A1 plasmid DNA transfection to reverse fibrotic degeneration and support disc regeneration. (July 2017) - Feng, Ganjun; Zhang, Zhanpeng; Dang, Ming; Zhang, Xiaojin; Doleyres, Yasmine; Song, Yueming; Chen, Di; Ma, Peter X.
Abstract: Safe and efficient gene therapy is highly desired for controlling pathogenic fibrosis of nucleus pulposus (NP) tissue, which would result in intervertebral disc (IVD) degeneration and disability if left untreated. In this work, a hyperbranched polymer (HP) with high plasmid DNA (pDNA) binding affinity and negligible cytotoxicity is synthesized, which can self-assemble into nano-sized polyplexes with a "double shell" structure that can transfect pDNA into NP cells with very high efficiency. These polyplexes are then encapsulated in biodegradable nanospheres (NS) to enable two-stage delivery: 1) temporally-controlled release of pDNA-carrying polyplexes and 2) highly efficient delivery of pDNA into cells by the released polyplexes. These biodegradable NS are co-injected with nanofibrous spongy microspheres (NF-SMS) to localize the cellular transfection of the pDNA encoding orphan nuclear receptor 4A1 (NR4A1), which was recently reported as a therapeutic agent to delay pathogenic fibrosis. It is shown that HP can transfect human NP cells efficiently in vitro with low cytotoxicity. The two-stage delivery system is able to present the polyplexes over a sustained time period (more than 30 days) in the tail of a rat. The NR4A1 pDNA carried by the HP polyplexes is found to therapeutically reduce the pathogenic fibrosis of NP tissue in a rat-tail degeneration model. In conclusion, the combination of the two-stage NR4A1 pDNA delivery NS and NF-SMS is able to repress fibrosis and to support IVD regeneration.